Introducing Japanese religion - Ellwood, Robert S. (World religions series, 2008)
"Introducing Japanese Religion" also includes illustrations, lively quotations from original sources, learning goals, summary boxes, questions for discussion, and suggestions for further reading, and a glossary, to aid study and revision.